Potential uses of public-private-people-partnerships for improving the health services in Egypt: A case study of "Egypt free from virus C" program - Farahat, Sarah Mohamed (AUC Knowledge Fountain, 2015)
Egypt’s healthcare system focuses on providing treatment at the expenses of the strategies of prevention due to the budget limitations. This thesis studies the adopting of Public Private People Partnership (4Ps) model as people oriented development approach that evolved out of the Public Private Partnership (3Ps) approach to improve healthcare infrastructure and its services. The 4Ps model is a partnership that embraces collaboration between public sector and private sector; while engaging the people represented by civil society throughout strategy making and implementation. This approach was conducted through collaboration between the Ministry of Health and Population and Telecom Egypt, with civil society engagement through Misr El Kheir Foundation in “Egypt Free from Virus C” program that aims at reducing the percentage of Virus C infections. The thesis studies the potential of applying the 4Ps model adopted in this program in the healthcare sector in the Egyptian context. Based on both the literature and the case study, the thesis concludes that the 4Ps model can be used as a development model to upgrade and advance healthcare services in Egypt. Despite the challenges that faced implementing the program, the findings indicate that the (4Ps) model is a successful developmental approach for the developing countries to deal with their developmental challenges.